THE POTENTIAL OF TOURISM VILLAGES BASED LEARNSCAPE AS A GEOGRAPHY LEARNING RESOURCE (CASE STUDY IN PANGLIPURAN, BALI) - Bambang Sigit WIDODO; Hendri PRASTIYONO; Wiwik Sri UTAMI; Indah PRABAWATI; Jauhar WAHYUNI; Carmela S. DIZON (Geo Journal of Tourism and Geosites)
This research aims to assess the potential of tourism village based learnscape (case study in Penglipuran, Bali) as a geography learning resource. To describe the management of cultural tourism based on local wisdom in Panglipuran village as a learning resource, especially cultural, economic, social and tourism geography. Using a qualitative approach, this research involved traditional leaders, religious leaders, and the community in Panglipuran village as key informants and resource persons. Data collection in this study used in-depth interviews, participant observation and documentary studies. While data analysis uses the stages of data collection, data reduction, data presentation, verification and conclusions. The results show that Penglipuran tourist village has great potential as a learnscape that provides a unique and meaningful geography learning experience related to Balinese culture. Learnscape elements such as traditional architecture, traditional ceremonies, and interaction with local communities contribute significantly to tourist satisfaction and intention to return. This research concludes that the development of learnscape-based tourism villages can be an effective strategy as a geography learning resource, increasing the attractiveness of Penglipuran village tourism to be revisited and provide economic benefits to the local community.